2022
DOI: 10.56430/japro.1174674
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analysis and Macroeconomic Variable Determinants of Egg Production in Nigeria

Abstract: The daily animal protein intake of an average Nigerian is far less than the World Health Organization recommended minimum standard. The egg is the cheapest and most affordable animal protein source in Nigeria, but its production has not been able to match the increasing demand capacity. Premised on the above facts and to identify ways to intensify egg production, the study was specifically designed to examine the trend in egg production and establish the relationship between egg production and selected macroec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…A study has revealed that the amount of credit allocated to the agricultural sector, per capita income, and corn and chicken meat production levels positively influence egg production in both the short and long term. Conversely, the consumer price index exhibits a negative correlation with egg production in both time frames (Akpan and Nkanta, 2022). Examining developed countries, it is evident that they focus on demand-driven research rather than studying input-output relationships.…”
Section: Discussionmentioning
confidence: 99%
“…A study has revealed that the amount of credit allocated to the agricultural sector, per capita income, and corn and chicken meat production levels positively influence egg production in both the short and long term. Conversely, the consumer price index exhibits a negative correlation with egg production in both time frames (Akpan and Nkanta, 2022). Examining developed countries, it is evident that they focus on demand-driven research rather than studying input-output relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Lumen (2020) established that the degree to which institutional financial support is perceived to be a problem (especially for agripreneurs) could significantly affect their intention to venture into agripreneurship. Akpan (2010) also noted that factors affecting rural Nigerian youth involvement in agriculture include inadequate availability of credit facilities, lack of agricultural insurance, initial capital, and production inputs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Financial Support Akpan, 2010;Lumen, 2020 Markets for Agric Products Kanan, 2012;Shiwa, 2014;Abera et al, 2020;Jeil, et al, 2020;Jha, et al 2020 Infrastructural Deficiency Kumar, 2019, Muhammad-Lawal, et al, 2009 Agriculture Intervention and Entrepreneurship Programs Umeh et al, 2020;Adeyanju et al, 2021;Adesina & Favour, 2016. Family Income Background Umeh et al, 2020;Nnadi and Akwiwu, 2008.…”
Section: Institutionalmentioning
confidence: 99%
“…Despite the numerous incentives for the country's poultry industry, the majority of Nigerians are experiencing a decline in animal protein intake (Akpan and Udo, 2021;Akpan and Nkanta, 2022;Akpan, 2022). Due to the advantages of poultry farming over other areas of livestock farming, the sub-sector can provide reliable cheap meat sources if resources are utilized appropriately.…”
Section: Introductionmentioning
confidence: 99%